Design of a Novel Decimal to Multicode Converter in QCA Technology - Farhad Fouladinia; Mohammad Gholami (Journal of Electrical and Computer Engineering)
Researchers are always looking for the improvement of existing methods. Today, CMOS technology is widely used, which has some advantages and disadvantages. One of the alternative methods for CMOS technology is QCA technology which compared to CMOS, has the advantages of low energy consumption and small occupied area. In this paper, by using the concepts and methods of QCA technology, a digital code converter is presented. In this converter, a new gate is used, which can produce outputs such as 4-input AND, 4-input OR, 4-input NAND, and 4-input NOR. The proposed converter has 10 inputs and 12 outputs. The 10 inputs are decimal numbers from 0 to 9, producing the output equivalent to excess-3, BCD, and gray codes. One of the advantages of this circuit is providing three different codes per input in just one circuit. In addition, due to the use of the new 4-input gate, the occupied area and the number of used cells were minimized. Simulations were performed by using QCADesigner-E version 2.2, and outcomes illustrated that the occupied area is equal to 0.29 μm2 and 380 QCA cells with 7 clock phases are used. The energy dissipation of the presented circuit is 171 meV. Also, given the favorable performance exhibited by the 4-input gate across various measurement parameters, it possesses the capability to be efficiently employed within larger and intricately designed circuits.